Challenging power through social media - Rodwell Makombe; Grace Temiloluwa Agbede (Communicare)
Robert Mugabe has ruled Zimbabwe since independence in 1980. However, in recent years, he has faced serious resistance from ordinary citizens. This article examines subversive internet memes that were created by ordinary Zimbabweans and posted on social media in the aftermath of Robert Mugabe’s collapse at the Harare International airport on 4 February 2015. Firstly, the study reads internet memes of the Mugabe fall as forms of resistance to the regime. Secondly, it interrogates the methods that internet memes use to challenge official discourse. Thirdly, the study critically analyses the various ways in which internet meme creators imagine and represent Zimbabwe under the Mugabe regime. The article argues that internet memes of the “Mugabe fall” express subversive views that undermine the regime through humour, exaggeration, satire and other stylistic devices. Internet memes present an alternative discourse that counters the official narrative promoted by the regime.